The Effect of Short Sales Constraints on SEO Pricing - Charoenwong, C. (Institutional Knowledge at Singapore Management University, 2006)
This article examines the influence of SEC’s Rule 105, Regulation M on the information environment surrounding the offer day of a seasoned equity offering (SEO). The results of this study show that the constraints on short sales imposed by the Rule inhibit informed trading for offers with private adverse information and without listings on the options market. These constraints also contribute to a substantial increase in information asymmetry and market makers’ relatively more sensitive response to seller-initiated trading. After controlling for other potential determinants of SEO discounts, such as price pressure and transaction cost savings, the results show that the increase in information asymmetry just before an offer day has a significant impact on the value discount of an SEO. The Rule’s restrictions on informed trading appear to cause overpricing of stocks for which traders have access to private adverse information, which increases the pressure to sell on the offer day.